Echocardiographic identification of aorta and main pulmonary artery in complete transposition. - Houston, A B (1978)
No completely reliable echocardiographic technique has been described for the separate identification of the aorta and main pulmonary artery in complete transposition of the great arteries. A mechanical wide-angle (60 degrees) sector scanner has been applied to this problem in 17 infants and young children, including 8 newborns before angiocardiography. In all patients a longitudinal scan (saggital section) identified the main pulmonary artery by its directly posterior course immediately beyond the pulmonary valve, and the aorta by its retrosternal course upwards before turning posteriorly above the main pulmonary artery. In addition, a high transverse scan showed the precise spatial relation of the great arteries, and, in 11 of the 17, tilting the scanning plane upwards showed branching of the main pulmonary artery. In 8 infants examined with M-mode echocardiography, an upward sweep from the pulmonary valve showed abrupt termination of the echo from the posterior wall coinciding with the posterior arching of the main pulmonary artery.